2014
DOI: 10.11648/j.ajpn.20140201.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Elderly Depression among Rural Bangladeshi Individuals

Abstract: Background: Depression is a chronic disorder, which often remains undiagnosed. There is a gross lack of evidence-based information about depressive illnesses among adult individuals from rural Bangladesh. Objective: The present study aimed to determine the factors that are associated with depressive illness but remain undiagnosed among rural healthy adult individuals. Methodology: A cross-sectional study was conducted in the Demographic Surveillance System area of rural Mirzapur sub-district, during April to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 31 publications
10
18
1
1
Order By: Relevance
“…3 In Bangladesh, older persons (those aged 60 or above) had a 2.79 times higher risk of depression than middle-aged persons (those aged 40-59). 4 Older persons show a greater preference for religious activities than younger people. Religiosity is defined as perceptions of religious beliefs, worship, and prayer.…”
Section: Introductionmentioning
confidence: 99%
“…3 In Bangladesh, older persons (those aged 60 or above) had a 2.79 times higher risk of depression than middle-aged persons (those aged 40-59). 4 Older persons show a greater preference for religious activities than younger people. Religiosity is defined as perceptions of religious beliefs, worship, and prayer.…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors may contribute to older persons' depression. A previous study [7], conducted in a central district near the capital city, found that female older persons with low monthly incomes were at a higher risk of depression than wealthy or high-income, middle-aged males. However, these results may not be generalizable to other districts of Bangladesh due to geographic, demographic and socioeconomic differences.…”
Section: Introductionmentioning
confidence: 92%
“…Depression is a serious public health problem in both developed and developing countries. In Bangladesh, a study found that older persons had a 2.79 times higher risk of depression that then middle-aged (40-59 years) [7]. It is important to investigate older person's depression.…”
Section: Introductionmentioning
confidence: 99%
“…Depression in old age can create many problems, including carrying out activities of daily living; increased morbidity and suicide [11]; decreased physical, cognitive and social functioning; and greater self-neglect [12]. In Bangladesh, older persons (aged 60 or above) had a 2.79 times higher risk of depression compared to middle-aged persons (aged 40-59) [13]. To reiterate, studies [6,13] have indicated that older persons in Bangladesh were suffering from sleep problems and depression.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, older persons (aged 60 or above) had a 2.79 times higher risk of depression compared to middle-aged persons (aged 40-59) [13]. To reiterate, studies [6,13] have indicated that older persons in Bangladesh were suffering from sleep problems and depression. However, their sleep problems were not measured using instruments.…”
Section: Introductionmentioning
confidence: 99%